Smart Agriculture in Afghanistan Using the Internet of Things: Challenges and Solutions - Hassand, Allah Mohammad (Journal of Natural Sciences – Kabul University)
As the global population continues to grow, securing food resources has become increasingly critical, particularly in regions facing water scarcity, energy shortages, and limited arable land. Traditional farming methods are no longer sufficient to meet these demands. Consequently, the integration of information technology and the Internet of Things (IoT) has gained significant attention in modern agriculture. IoT technology enables farmers to access real-time, reliable data on critical factors such as seed quality, soil moisture, and soil pH, enhancing agricultural efficiency and productivity. This study, conducted using a review-based approach, highlights the crucial role of IoT in smart farming. However, despite its advantages, smart farming in Afghanistan faces several challenges, including the need for a stable internet infrastructure and expertise in data analysis. To overcome these obstacles, the Ministry of Agriculture, agricultural institutions, and other relevant organizations should implement awareness programs and educational seminars to promote the adoption of smart farming technologies.